Shoot/do not shoot – what are the influences? The police recruit perspective - Davies, Amanda Jane (Policing and society, 2017)
The often highly public controversy that surrounds police use-of-force which can and on occasion does lead to the death of members of the community continues unabated. In the aftermath of the 2014 deaths of Michael Brown and Eric Garner in the USA and in Australia the death of lone gunman Man Haron Monis as a result of police use-of-force research which contributes to police training in this complex area remains of interest to police organisations and the communities they serve. This paper presents findings from a case study which followed the learning journey of police academy recruits in the development of use-of-force decision-making skills with specific focus on their experience in a simulation exercise - designed to require use-of-force in most circumstances. A three phase data collection process included, voluntary completion of a pre- and post-simulation survey by a class of 372 participants; and interviews with 15 participants 3-4 months post-simulation in their capacity as operationally deployed police officers. Interviewees were purposively selected to capture a cross sample of workplace location, age groupings and with a balance of gender representation. The findings from the study contribute to understanding (a) the factors which influence and develop a police recruit's use-of-force decision-making capability; (b) the influence of use-of-force simulation experiences on future operational practice and (c) the influence of less lethal tactical option skill application. Research participation offered opportunity for participants to build their reflective practitioner skills as they step into the unpredictable world of operational policing.